Answer:
see explanation
Explanation:
Given y varies inversely with x then the equation relating them is
y =
← k is the constant of variation
(1)
To find k use the condition x = 5, y = 10, thus
k = yx = 10 × 5 = 50
------------------------------------------------------
(2)
y =
![(k)/(x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/aj90vf3mk5pt7yvvf5jxye2jg6ixk1od1r.png)
To find k use the condition y = 8, x = 10
k = yx = 8 × 10 = 80
y =
← equation of variation
when y = 4, then
4 =
( multiply both sides by x )
4x = 80 ( divide both sides by 4 )
x = 20
---------------------------------------------------------
(3)
y =
![(k)/(x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/aj90vf3mk5pt7yvvf5jxye2jg6ixk1od1r.png)
To find k use the condition y = - 5, x = 20
k = yx = - 5 × 20 = - 100
y =
← equation of variation
when y = - 4, then
- 4 =
( multiply both sides by x )
- 4x = - 100 ( divide both sides by - 4 )
x = 25